Peran Publikasi dalam Event Our Ocean Conference 2018 oleh Kementerian Kelautan dan Perikanan - Alya Salma Nabila; Dewi Winarni Susyanti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
Publication is one of an important aspect for a successful event. Public relations officers are the one that doing this activity. This research is using qualitative method and it discuss about how publication affect the amount of delegation that will join Our Ocean Conference 2018 by Ministry of Marine and Fisheries Indonesia. Publication in this research is using visual media such as digital news platform, banner, billboard, e-flyer and send an email to the targeted delegation. It also use audio-visual media as a publication such as videotron in front of the building of Ministry of Marine and Fisheries Indonesia and creating social media account such as Instagram, Twitter, Facebook, Website, and a teaser video on KKP News Youtube Channel. The targeted delegation for this event is 1.500 delegations from around the world and from various stakeholders too including Head of States, non-government organization, researcher, student and people who cares about our ocean health.